Transfemoral biopsy: a routine procedure after orthotopic heart transplantation for dilated cardiomyopathy in a patient with persistent left superior vena cava and hypoplastic right superior vena cava - Ghodsizad, Ali; Zugck, Christian; Karck, Matthias; Ruhparwar, Arjang; Bordel, Viktor (The heart surgery forum, 2012)
Introduction: The increasing number of end stage heart failure patients has caused a high number of transplant candidates, including patients with concomitant other cardiac abnormalities. Congenital heart failure can exhibit changes in a variety of anatomic landmarks, and performing heart transplantation in this setting can be challenging. Monitoring for possible rejection is done via intramyocardial biopsies. Here the difficulties arise from variations in anatomic structures.Background: We present a case of a persistent left superior vena cava discovered intraoperatively during heart transplantation. The patient was a 45-year-old man who underwent transplantation for a severely reduced left ventricular function, along with a high left ventricular end-diastolic pressure and and end stage heart failure.Discussion: In previous cases, the biopsy was performed by means of left-sided transjugular venous access. Bearing the well-known complications in mind, we chose the transfemoral access so we could take biopsies postoperatively. Biopsies in patients with persistent left vena cava should routinely be performed using the transfemoral access.